2021
DOI: 10.1002/mmce.23026
|View full text |Cite
|
Sign up to set email alerts
|

A low profile wideband pattern reconfigurable metasurface antenna

Abstract: A low profile electrically controlled pattern reconfigurable antenna with wide bandwidth is proposed in this article. The antenna is designed on two closely stacked substrates with a very low profile of 0.04λ0. On the top layer of the design is a periodic metasurface and two parasitic strips, and on the bottom layer is a metallic ground etched with rectangle slot. The feed line is designed on the middle layer to excite the metasurface patch antenna. Eight pin diodes are mounted between the parasitic metallic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…The table shows that the proposed reconfigurable metasurface antenna has a smaller size than References [17,19] which can better meet the miniaturization requirements of the low-frequency radar system. Moreover, the proposed antenna has a higher peak gain and larger beam scanning angles than References [21][22][23]. In addition, the reconfigurable metasurface antenna has lower cost.…”
Section: Beam Forming Performancementioning
confidence: 95%
See 2 more Smart Citations
“…The table shows that the proposed reconfigurable metasurface antenna has a smaller size than References [17,19] which can better meet the miniaturization requirements of the low-frequency radar system. Moreover, the proposed antenna has a higher peak gain and larger beam scanning angles than References [21][22][23]. In addition, the reconfigurable metasurface antenna has lower cost.…”
Section: Beam Forming Performancementioning
confidence: 95%
“…A single function system cannot meet the requirement of working and causes waste resources. In order to solve above problems, some researchers have proposed loading active devices such as PIN diode, Micro‐Electro‐Mechanical‐Systems on metasurfaces 15–24 . The type of metasurfaces is called reconfigurable metasurfaces, in which the binary states are usually represented by two different values of phases, amplitudes or polarizations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 To realize wide-angle scanning in a phased-array antenna, the pattern reconfiguration technique has been proposed. [2][3][4][5][6][7] It has been found that combining the pattern reconfiguration technique with phased-array technology can overcome limitation and enable a variety of applications such as vehicle identification systems to be developed.…”
Section: Introductionmentioning
confidence: 99%
“…Based on phase reconfigurable synthesized transmission line (PRSTL) feeding structures, 15 a planar printed dipole radiator generates four radiation beams by switching five variable capacitance diodes. Moreover, micro‐strip patch antennas through implanting diagonal shorting probes, 9 introducing complementary split‐ring resonator (CSRR) defected ground structures, 10 loading vacarctor, 16 and using periodic meta‐surface 17 are also good candidates for realizing multi‐beam re‐configurability. Unfortunately, due to the narrow band characteristics of the micro‐strip radiators, most of them are exposed to limited operation bandwidth, usually only a few percent.…”
Section: Introductionmentioning
confidence: 99%